Modern administrative law of the Republic of Uzbekistan: new approaches to understanding the essence and structure (Journal of actual problems of jurisprudence, 2020)
This article is devoted to the analysis of a number of problems of modern administrative law of the Republic of Uzbekistan. At the same time, various approaches to solving these problems are investigated in the legislation of foreign countries, the opinions of various scientists on the issues under study are examined. The article provides a legal analysis of the reform of the public administration system, improving the institutional and organizational-legal foundations of the activities of executive bodies; issues of improving the system of public services; the problems of forming an effective system of professional civil service; administrative process problems. Based on the analysis of these problems, proposals are put forward on the need to adopt a special law on executive authorities of the Republic of Uzbekistan; on supplementing the Law of the Republic of Uzbekistan “On local government” with the norm relating to the concept of “local government”; on streamlining administrative procedures in the field of activity of executive authorities; on the need to adopt the law “On Public Service”. Key words: law, executive branch, public service, administrative procedures, public services.